PANDANGAN MENUTUP AURAT PASANGAN DALAM PERSPEKTIF AL-QUR'AN: STUDI TENTANG AYAT-AYAT LIBAS (PAKAIAN) - Yuhana, Laili (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Abstract. Libas can mean clothing, mixing and covering. Libas originally meant cover. Whatever is covered, the function of clothing as a covering is very clear. However, it should be noted that this does not necessarily mean "covering the private parts" because rings that cover part of the finger are also called libas. It is not uncommon to find many families, especially married couples, who do not understand the meaning of clothing for married couples. So in this article the author will discuss the meaning of libas contained in the Al-Qur'an. From several functions and meanings of libas, the author will discuss the concept of libas for married couples contained in the Qur'an. The results of the analysis can be stated that regarding the meaning of clothing (libas) for husband and wife, namely, if clothing (libas) is able to protect against stings. hot and cold, then husbands towards their wives and wives towards their husbands must also be able to protect their partners from the crises and difficulties they face. Meanwhile, his istinbath method regarding clothing (libas) for couples is tafsir tahlili. He explained the verses of the Qur'an in terms of editorial accuracy, then compiled the contents with beautiful editorials that emphasized the guidance of the Qur'an for human life and connected the meaning of the verses of the Qur'an with the natural laws that occur. in society. Where in this case the function of clothing as a cover for the private parts is the most important function for humans to maintain cover by covering body parts and human physical deficiencies. So, husband and wife must complement each other and take care of each other's shortcomings.   Keywords. Covering Aurat, Al-Qur'an, Libas Verses